Fiber Optic Sensing in Spacecraft Engineering: An Historical Perspective From the European Space Agency - McKenzie, Iain; Ibrahim, Selwan; Haddad, Emile; Abad, Silvia; Hurni, Andreas; Cheng, Lun K. (Frontiers in Physics, 2021)
For over two decades the European Space Agency has investigated the possibility of using fiber optic sensors in spacecraft engineering as tools to advance the monitoring and control of spacecraft. The applications have been diverse covering both launcher and satellite applications and encompassing environments from cryogenic to high temperature re-entry applications. The aim of this review is to capture the history and status of fiber optic sensors for space applications demonstrating the breadth of applications that have been studied and the lessons learnt along the way. Finally, it is the intention of this review to look forward, pointing to how this technology can be used in the future and identifying what are the key remaining challenges to its further successful exploitation.